Controlled clinical trial of teacher-delivered Cognitive Behavioural Therapy (CBT) for adolescents with clinically diagnosed depressive disorder in Nigeria. Issue 1 (2nd January 2022) - Are, Amos; Olisah, Victor; Bella-Awusah, Tolulope; Ani, Cornelius
Abstract: Most depressed adolescents in Low and Middle Income Countries (LMICs) like Nigeria have no access to psychological intervention due to lack of trained mental health professionals. This huge treatment gap could be bridged by using non-mental health professionals such as teachers to deliver the interventions. This study evaluated a teacher-delivered Cognitive Behavioral Therapy (CBT) programme for depressed adolescents in Nigeria. Forty adolescents (aged 13–18 years) with clinically diagnosed depressive disorder were recruited from two schools (20 from each school). One school was balloted as intervention and the other as control. The intervention group received five sessions of manualised group-based CBT delivered by two teachers who were trained and supervised by a psychiatrist. Primary outcome was BDI score at week 6. Controlling for baseline BDI score, the intervention group had significantly lower post-intervention depressive symptoms {Means 4.60 vs 17.05; t = 4.13; p  = 0.0001, F(1, 39) = 16.76, p  = 0.0001, Effect Size (Cohen's d) = 1.3}. Eighty-percent of the intervention group achieved remission compared with only 15.8% of the controls ( p  < 0.0001). To our knowledge, this is the first study of a teacher-delivered CBT programme for clinically depressed adolescents in a LMIC. The intervention was feasible, well received and showed promising efficacy.